HFE genotypes, haemochromatosis diagnosis and clinical outcomes at age 80 years: a prospective cohort study in the UK Biobank - Luke C Pilling; David Melzer; Janice L Atkins; Mitchell R Lucas; Jeremy D Shearman (BMJ Open)
Objectives HFE haemochromatosis genetic variants have an uncertain clinical penetrance, especially to older ages and in undiagnosed groups. We estimated p.C282Y and p.H63D variant cumulative incidence of multiple clinical outcomes in a large community cohort.Design Prospective cohort study.Setting 22 assessment centres across England, Scotland, and Wales in the UK Biobank (2006–2010).Participants 451 270 participants genetically similar to the 1000 Genomes European reference population, with a mean of 13.3-year follow-up through hospital inpatient, cancer registries and death certificate data.Main outcome measures Cox proportional HRs of incident clinical outcomes and mortality in those with HFE p.C282Y/p.H63D mutations compared with those with no variants, stratified by sex and adjusted for age, assessment centre and genetic stratification. Cumulative incidences were estimated from age 40 years to 80 years.Results 12.1% of p.C282Y+/+ males had baseline (mean age 57 years) haemochromatosis diagnoses, with a cumulative incidence of 56.4% at age 80 years. 33.1% died vs 25.4% without HFE variants (HR 1.29, 95% CI: 1.12 to 1.48, p=4.7×10-4); 27.9% vs 17.1% had joint replacements, 20.3% vs 8.3% had liver disease, and there were excess delirium, dementia, and Parkinson’s disease but not depression. Associations, including excess mortality, were similar in the group undiagnosed with haemochromatosis. 3.4% of women with p.C282Y+/+ had baseline haemochromatosis diagnoses, with a cumulative incidence of 40.5% at age 80 years. There were excess incident liver disease (8.9% vs 6.8%; HR 1.62, 95% CI: 1.27 to 2.05, p=7.8×10-5), joint replacements and delirium, with similar results in the undiagnosed. p.C282Y/p.H63D and p.H63D+/+ men or women had no statistically significant excess fatigue or depression at baseline and no excess incident outcomes.Conclusions Male and female p.C282Y homozygotes experienced greater excess morbidity than previously documented, including those undiagnosed with haemochromatosis in the community. As haemochromatosis diagnosis rates were low at baseline despite treatment being considered effective, trials of screening to identify people with p.C282Y homozygosity early appear justified.